Knowledge based urban development: An approach to innovation districts based on education - Ponce-Lopez, Roberto; Peraza-Mues, Gonzalo; Gómez-Zaldívar, Fernando; Membrillo-Hernández, Jorge; Acuña-López, Alejandro; Caratozzolo, Patricia (Frontiers in Education, 2023)
Education is a concept that encompasses not only the teaching-learning process but also the conditions, environment, and facilities in which it takes place. Education is a precondition to development because it serves as a society’s primary engine of innovation. Therefore, the concept of a space designated as an Innovation District is essential for the creation of Sustainable Cities since it is in such spaces that jobs are created and new markets specializing in products and high-added value services emerge. However, in the past, successful innovation districts have generally been found in developed countries, which have sufficient resources to invest in projects of this magnitude. In this paper, we analyze the role of higher education within developing countries that seek to create innovation districts. We propose a conceptual and methodological framework in which quantitative methods--in the areas of industrial analysis, spatial-urban analysis, and design of educational models adapted to the needs of specific industries--are combined into a collaborative strategy based on the Triple Helix model. We study the city of Querétaro, in central Mexico to answer this question. The results of our case study suggest that developing countries can best maximize their chances of success by encouraging an explicit collaboration between industry and education. Such a collaboration would be based on matching educational competencies with opportunities for industrial reconfiguration in order to carefully select the location for the new district.